Spatio-temporal periodic behavior mining algorithm for social networks - Yu-peng HU; Hao LUO; Ya-ping LIN; Zheng QIN; Bo YIN (Tongxin xuebao)
A hierarchical bipartite graph based model and a mining algorithm were presented to obtain the potential spatio-temporal periodic behavior,meanwhile avoided the subset omitting problem in previous schemes.Then the location analysis algorithm was designed to achieve the nearly inimum location dominating subset,it could monitor the small portion of the locations as early as possible.Finally experiments results show that the algorithms can find out the periodic location set as well as obtain nearly minimum location dominating subset,so as to cover the major portion of objectives using those popular locations.